The Role of Educational Level in Moderating The Influence of Job Training and Communication Skills on Employee Work Effectiveness - Riny Chandra; Tengku Putri Lindung Bulan (Inovbiz: Jurnal Inovasi Bisnis, 2023)
To determine the effect of job training and communication skills on employee work effectiveness and the role of education level in moderating the relationship between job training and communication skills on employee work effectiveness at the Disperindagkop and UKM Kota Langsa.  Using a qualitative design that was quantified with a saturated sampling method, namely, all PNS of the Department of Industry and Trade and UKM of Langsa City were used as research samples using the PLS-SEM approach.  It Shows that job training has a negative and insignificant effect on employee effectiveness. In contrast, communication skills have a positive and significant effect on employee effectiveness, and the interaction of education level with job training has a positive and insignificant effect on employee effectiveness. The interaction of education level with communication skills has a positive and significant effect on the work effectiveness of employees at the Disperindagkop and SMEs in Langsa City.